Design and numerical study of active cooling device for high temperature oil and gas wells based on regenerative refrigerator - Ke Liu; Wenkai Gao; Jinhui Fan; Hao Peng; Kang Guan; Song Tang; Liang Zhang (Scientific Reports)
Abstract The high temperature resistance of measurement while drilling (MWD) instruments hinders the development of drilling technology. This article adopts a turbine driven refrigeration power system to overcome the problem of difficulty in inputting external energy during the cooling process of the refrigerator. Adopting a regenerative refrigeration system to reduce the impact of the radiator on the circuit compartment. We design active cooling systems with sidewall cabin and central water eye, and studied their heat transfer characteristics using numerical methods based on Fluent 21.0. The research results indicate that the central water eye active cooling system has better heat resistance performance and a lower heat load of 8.65 W for the refrigeration unit. For the central water eye type, reducing the surface radiation coefficient of the parts results in less external heat leakage change.